Biologically Important Areas II for cetaceans within U.S. and adjacent waters – Hawaiʻi Region - Kratofil, Michaela A.; Harnish, Annette E.; Mahaffy, Sabre D.; Henderson, E. Elizabeth; Bradford, Amanda L.; Martin, Stephen W.; Lagerquist, Barbara A.; Palacios, Daniel M.; Oleson, Erin M.; Baird, Robin W. (Frontiers in Marine Science, 2023)
In this assessment we incorporated published and unpublished information to delineate and score Biologically Important Areas (BIAs) for cetaceans in the Hawaiʻi region following standardized criteria. Twenty-six cetacean species have been documented in Hawaiʻi. Eleven odontocete species have distinct small populations resident to one or more island areas: rough-toothed dolphins, pantropical spotted dolphins, common bottlenose dolphins, spinner dolphins, short-finned pilot whales, false killer whales, pygmy killer whales, melon-headed whales, Blainville’s beaked whales, Cuvier’s beaked whales, and dwarf sperm whales. Eight species of mysticetes have been documented, although their occurrence and behavior are poorly understood, with the exception of breeding humpback whales and, more recently, common minke whales. Thirty-five BIAs were delineated or revised from the initial 2015 effort: 33 for small and resident odontocete populations and two for humpback whale reproductive areas. Hierarchical BIAs reflecting core areas of use or population-specific ranges were delineated for nine species. Reproductive watch list areas were designated for common minke whales in the main Hawaiian Islands (MHI) and humpback whales in the Northwestern Hawaiian Islands (NWHI); these areas did not meet the criteria for a BIA due to limited supporting information. All but three BIAs were in the MHI, reflecting the disparities in research effort between this region and the NWHI. Spatial extents of BIA boundaries ranged from 457 km2 to 138,001 km2 (median = 8,299 km2). Scores (range: 1-3) for Data Support and Boundary Certainty were moderate to high (mean = 2.40 and 2.43, respectively), while Intensity and Importance scores were slightly lower (mean = 1.94 and 1.89, respectively). Many of the Hawaiʻi species have been extensively studied over several decades; accordingly, this region ranks among the highest in terms of Data Support relative to other regions. BIAs presented here describe known ranges of small resident populations, intensities of use, and uncertainties in important areas for cetaceans in Hawaiʻi based on the best available data, and have also revealed knowledge gaps to guide future research efforts.